The Role of Parents in Introducing Sex Education to Early Childhood - Mei Ratnasari, Eka; Indria, Anita; Dwi Utami, Rahmi (Journal of Islamic Early Childhood Education, 2024)
The spread of cases of sexual violence against children committed by those closest to them shows that they need to introduce early childhood sex education. Parents paid less attention to the introduction of sex education for children because they felt that sex education was taboo and did not need to be introduced to children from an early age. Most parents leave their children's education to school, this understanding makes parents pay less attention to the education that children receive, including sex education, even though parents are the closest and most trusted people to children. This research uses a descriptive qualitative approach. Data collection was carried out using interviews, observation, and documentation. The research subjects used 15 parents who worked and had children aged 3-6 years. The validity of the data used by data triangulation. The results showed that the implementation of sex education in early childhood should start from the closest person, parents provide introduction and learning using various methods to make the process of introducing sex education easier for children. Providing an understanding of children related to sex education is expected to protect children from the dangers of sexual violence.